Single blade installation of offshore wind turbines: A statistical model of motion maxima of offshore wind turbine components during installation - Ströer, Lena (Zenodo, 2021)
In this work, we analyzed, how the single blade installation tool (SBIT) and the tower are moving during an installation process. Based on measured accelerations (measurement campaign during installation of Trianel Windpark Borkum II (2019- 2020) wind farm [1]) of the blade lifting device and the turbine’s nacelle in combination with the environmental conditions, we determined the conditions of the entire system during single blade installation. The oscillating behavior of the tower and the SBIT before the first contact with the tower based on the data of the measurement campaign was described. A statistical model was created to investigate how the turbine components move conditional on wind and wave parameters. The statistical model for the nacelle’s and SBIT’s movement describes the maximum deflection in blocks of 1 minute conditional on wind and wave parameters. These block maxima have less serial correlation than individual responses and will be described by a generalized extreme value distribution.The distribution's parameters are described by dependence functions conditional on the environmental phenomena wind and waves. This results in a model consisting of conditional statistical distributions. Finally, the model allows to determine on when to install offshore wind turbines and to better exploit weather windows. To reproduce our results, we refer to the file "00_README_MasterThese_LenaStröer.txt". We do not claim our results to be extensive: In case of question or encountering any problems with the codes please contact us. [1] Sander, Aljoscha. (2020). Oscillations of Offshore Wind Turbines undergoing Installation I: Raw Measurements (Version 1) [Data set]. Zenodo. https://doi.org/10.5281/zenodo.4141208 : Note, that our work is based on the measurement campaign during the installation of the Trianel Windpark Borkum II (2019- 2020) wind farm. Additional information and the original data can be found here: [1] Sander, Aljoscha. (2020). Oscillations of Offshore Wind Turbines undergoing Installation I: Raw Measurements (Version 1) [Data set]. Zenodo. https://doi.org/10.5281/zenodo.4141208 : {"references": ["Sander et al. (2020a): RELATIVE MOTION DURING SINGLE BLADE INSTALLATION: MEASUREMENTS FROM THE NORTH SEA in International Conference on Ocean, Offshore and Arctic Engineering, Florida, USA", "Sander et al. (2020b): MONITORING OF OFFSHORE WIND TURBINES UNDER WAVE AND WIND LOADING DURING INSTALLATION in EuroDyn 2020, Athens, Greece", "Haselsteiner et al. (2021): A. Haselsteiner, M. Frieling, E. Mackay, A. Sander, and K.-D. Thoben. \"Long-term re- sponse of an offshore turbine: How accurate are contour-based estimates\", 2021. doi: 10. 13140/RG.2.2.21422.64320."]}